(untitled) (Research, Society and Development, 2022)
The metabolic dysfunctions resulting from obesity are associated with endocrine function of adipose tissue and as the expansion of adipose tissue occurs, there is a synergetic increase of pro-inflammatory adipocytokines that exert effects on adjacent organs. These changes can be minimized with physical activity because it decreases the body adiposity, contributing factor to the decrease in pro-inflammatory adipocytokines and them harmful effects on body. An integrative review was carried out on platforms that provide academic data found in the main health journals: PUBMED, SCIELO and LILACS. Research was carried out over a five-year research period with the keywords: obesity, inflammation, physical exercise e experimental models. The results show that physical activity is effective in attenuating the inflammatory profile of animals reducing the harmful physiological responses that obesity and a sedentary lifestyle cause, such as insulin resistance, increase of HOMA-IR index, decrease of glucose intake capacity, increase of LDL-cholesterol levels, triglycerides, and action of pro-inflammatory cytokines, in addition to promoting favorable adaptations for a stable homeostatic framework through the prevailing polarization of macrophages 2 and improvement of the anti-inflammatory action in a systemic way. The aerobic protocols appear to predominantly cause beneficial responses in these indicators when compared to other types of resistance and combined protocols, especially when they are performed at high and moderate intensity.